2009
DOI: 10.1007/s12253-009-9190-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes of AXIN-1 and Beta-Catenin in Neuroepithelial Brain Tumors

Abstract: In the present study changes of components of Wnt signaling pathway--axin (AXIN1) and beta-catenin (CTNNB1) in a sample of 72 neuroepithelial brain tumors were investigated. AXIN-1 gene was tested by PCR/loss of heterozygosity (LOH). Immunostaining and image analysis revealed the quantity and localization of relevant proteins. Polymorphic marker for AXIN-1, showed LOH in 11.1% of tumors. LOH was distributed to 6.3% of glioblastomas, one was found in neuroepithelial dysembrioplastic tumor and one in medulloblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 21 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…Our previous study on beta‐catenin expression in neuroepithelial brain tumours of different grades strengthens the claim on Wnt signalling pathway's activity. We have shown that beta‐catenin was upregulated in 53.1% of samples.…”
Section: Discussionsupporting
confidence: 80%
“…Our previous study on beta‐catenin expression in neuroepithelial brain tumours of different grades strengthens the claim on Wnt signalling pathway's activity. We have shown that beta‐catenin was upregulated in 53.1% of samples.…”
Section: Discussionsupporting
confidence: 80%
“…Our previous study found β-catenin to be upregulated and transferred to the nucleus in astrocytic brain tumors ( 35 ). It was also demonstrated that the transcription factors of the Wnt signaling pathway were upregulated ( 7 ).…”
Section: Discussionmentioning
confidence: 97%
“…The three-dimensional structure of the full-length Axin will provide invaluable insights into the details regarding Axin auto-inhibition. On the other hand, increasing evidence indicates a role of Axin in nucleus (Nikuseva Martic et al, 2010; Pecina-Slaus et al, 2011; Schmitz et al, 2013; Willert and Jones, 2006). However, the precise role of nuclear Axin in Wnt signaling remains largely unknown, which warrants further investigation to facilitate our understanding of the function of nuclear Axin as well as its linkage to the cytoplasmic one.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%